The Influence Of Character Management And Learning Material Mastery On The Competence Of Public Vocational High School Teachers In Minahasa Regency - Imelda Moonik; Romi J. Mongdong; Zoya F. Sumampouw (PT. AHLAL PUBLISHER NUSANTARA, 2026)
This study investigates the influence of teacher character management and learning material mastery on the competence of public vocational high school teachers in Minahasa Regency, analyzing both factors partially and simultaneously. Employing a quantitative explanatory approach with a cross-sectional survey design, the study involved a sample of 105 teachers selected through proportional stratified random sampling from a population of 355 teachers across 11 public vocational high schools. The study utilized a validated Likert-scale questionnaire, with data analysis including descriptive statistics, validity and reliability tests, classical assumption tests, and multiple linear regression using SPSS version 27. The results revealed that teacher character management significantly positively affects teacher competence (t=18.914; p<0.001; R²=0.776), as does learning material mastery (t=18.690; p<0.001; R²=0.772), with both variables together explaining 77.7% of teacher competence variance (F=177.214; p<0.001; R²=0.777). The high correlation (r=0.997) between these two variables indicates a strong synergy between soft and hard competences in shaping teacher competence. The study concludes that the integrative soft-hard competence model is a powerful predictor of vocational teacher competence, recommending professional development programs that combine character development with enhancing TPACK/AI-TPACK mastery, along with policies for industrial internships of at least 40 hours per year for vocational teachers. Keywords: teacher character management, learning material mastery, teacher competence, TPACK, AI-TPACK, vocational high school, Minahasa